2023
DOI: 10.1007/s40123-023-00849-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Central Serous Chorioretinopathy in Elderly Subjects: Structure and Blood Flow Characteristics of Retina and Choroid

Pei Liu,
Haixin Fang,
Guangqi An
et al.

Abstract: Introduction With advancements in imaging technology, researchers have been able to identify more distinctive imaging features of central serous chorioretinopathy (CSC). However, existing research primarily concentrates on young patients aged 50 years and below, leaving a dearth of studies on elderly CSC patients. Previous studies indicate that elderly CSC patients may exhibit unique imaging characteristics and have a clinical prognosis that significantly differs from younger patients. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The reported male-to-female ratio ranges from 2 : 1 to 6 : 1 according to previous studies [ 22 ]. A recent study reported a similar male/female ratio of 2.3/1 (63/27) compared with our study [ 38 ]. The main reason was that after informing the patient that there could be adverse endocrine system events after spironolactone administration, such as feminization of male breasts and erectile dysfunction, some young male CSC patients refused to take it.…”
Section: Discussionsupporting
confidence: 90%
“…The reported male-to-female ratio ranges from 2 : 1 to 6 : 1 according to previous studies [ 22 ]. A recent study reported a similar male/female ratio of 2.3/1 (63/27) compared with our study [ 38 ]. The main reason was that after informing the patient that there could be adverse endocrine system events after spironolactone administration, such as feminization of male breasts and erectile dysfunction, some young male CSC patients refused to take it.…”
Section: Discussionsupporting
confidence: 90%
“… 1 3 In women, CSC presents typically at a slightly older age, generally after the menopause, between 50 and 69 years old, and often shows complications, such as secondary choroidal neovascularization. 7 , 8 Interestingly, pregnancy-associated CSC has been reported, most frequently in the third trimester, which coincides with elevated serum progesterone, estrogen, and cortisol levels. 9 , 10 Dysfunction of the choroidal vasculature has been thought to be part of the underlying pathology in CSC, based on clinical manifestations diagnosed with multimodal imaging (e.g.…”
mentioning
confidence: 99%